STRATEGI KOMUNIKASI IMAGE RESTORATION MANTAN NARAPIDANA KASUS NARKOBA DI MASYARAKAT KECAMATAN KEMBANGAN - Sandy Saputra; Ardan Achmad; Cakraningsih (Jurnal Komunikasi & Media Digital, 2025)
This research focuses on communication strategies for the image restoration of former drug convicts within their families and communities. The study employs a constructivist paradigm with a qualitative approach and descriptive method. A phenomenological perspective is applied, integrating data collection techniques such as in-depth interviews, observations, and documentation. Data validation is conducted through triangulation, while data analysis follows the Miles and Huberman technique. The findings reveal that image restoration strategies among former drug convicts are effectively implemented by applying William Benoit's theory of image restoration, which consists of five strategic approaches. The results demonstrate that these strategies contribute significantly to rebuilding public trust within the Kembangan District community. Among these, "Reducing Offensiveness" and "Corrective Action" emerge as the most crucial strategies. Through honesty (Reducing Offensiveness), sincere remorse (Reducing Offensiveness), and concrete change-oriented actions (Corrective Action), former drug convicts can successfully rehabilitate their damaged public image.